2010
DOI: 10.1007/s10526-009-9262-5
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of host behavioral defenses on parasitization efficacy of a larval and adult parasitoid

Abstract: Koinobiont parasitoid females when attacking host species are faced with barriers at various levels, host behavioral defenses represent one of these barriers. We present data of the effects of host behavioral defenses on host preference of larval and adult parasitoid. We quantified the effects of defensive behaviors of the exotic host, Harmonia axyridis (Pallas), and the indigenous host, Coleomegilla maculata lengi Timberlake (Coleoptera: Coccinellidae), on the handling time and attack preference of the indige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 53 publications
(80 reference statements)
3
40
0
Order By: Relevance
“…3), with reports both within its native range and in all invaded continents (Table 2), but parasitism and emergence rates are usually low in comparison with other host species (Maeta 1969b;Hoogendoorn and Firlej et al 2005Firlej et al , 2007Firlej et al , 2010Koyama and Majerus 2008;Ceryngier et al 2012;Minnaar et al 2014; Table 4). Koyama and Majerus (2008) demonstrated that D. coccinellae of Japanese origin developed in British H. axyridis more successfully (about 17% successful parasitism rate) compared to wasps of British origin (no successful parasitism).…”
Section: Tachinidae (Diptera)mentioning
confidence: 92%
See 3 more Smart Citations
“…3), with reports both within its native range and in all invaded continents (Table 2), but parasitism and emergence rates are usually low in comparison with other host species (Maeta 1969b;Hoogendoorn and Firlej et al 2005Firlej et al , 2007Firlej et al , 2010Koyama and Majerus 2008;Ceryngier et al 2012;Minnaar et al 2014; Table 4). Koyama and Majerus (2008) demonstrated that D. coccinellae of Japanese origin developed in British H. axyridis more successfully (about 17% successful parasitism rate) compared to wasps of British origin (no successful parasitism).…”
Section: Tachinidae (Diptera)mentioning
confidence: 92%
“…Despite its low suitability for development of D. coccinellae, H. axyridis is no less preferred for oviposition by this wasp than more suitable hosts (Hoogendoorn and Heimpel 2002;Koyama and Majerus 2008;Firlej et al 2010). Furthermore, interacting with D. coccinellae females, H. axyridis adults display more behavioural defenses than do the adults of suitable hosts, such as Coleomegilla maculata (DeGeer), which increases the handling time of the parasitoid and hence further reduces its fitness (Firlej et al 2010).…”
Section: Homalotylus Spp (Hymenoptera: Encyrtidae)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study shows that natural enemies are still unable to control populations of H. axyridis in Europe (Raak-van den Berg et al, 2014). In America also, despite the fact that D. coccinellae readily attacks H. axyridis, the success of the parasitism is very low and lower than on other coccinellid species, due to host behavioral defenses and unsuitability (Firlej et al, 2005(Firlej et al, , 2010.…”
Section: What Is the Phenology Of The Establishment And Spreading Of mentioning
confidence: 99%